Role of hedge funds in institutional portfolios : Florida retirement system - Elias, Jaan; Goetzmann, William N.; Baskin, Lloyd (London : Yale School of Management, 2016)
Institutional Investor magazine put "The Great Hedge Fund Experiment" on the cover of its June 2011 issue. Inside, the magazine described how in little over a decade, state pension funds had gone from considering hedge funds as "too risky and secretive" to embracing them in their asset allocation schemes. The magazine argued the interchange had left both pension funds and hedge funds profoundly changed.For Florida and other state pension systems, any allocation to hedge funds remained controversial, especially after the California Public Employees' Retirement System (CalPERS) decided to close its hedge fund program in 2014. CalPERS's decision reverberated throughout the industry - the New York Times described it as a watershed moment for the hedge fund industry - not only because the pension fund was the nation's largest, but also because CalPERS had actually been one of the first state pension funds to invest in hedge funds in 2002. However in 2014, CalPERS threw in the towel, arguing that hedge funds were too expensive, opaque, and complicated for its money managers. Many analysts agreed.
Originally published in Elias, J., Goetzmann, W., & Baskin, L. (2016). Role of Hedge Funds in Institutional Portfolios: Florida Retirement System. 16-016. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/florida-retirement-system.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Institutional Investor (Firm); California. -- Public Employees' Retirement System; Hedge funds -- Florida; Pension trusts -- Florida